The establishment of savings banks in colonial New Zealand 1840-1907. Issue 4 (12th September 2016) - Cardow, Andrew; Wilson, William Robert
Abstract : Purpose: This paper aims to highlight the reasons for the establishment of savings banks in New Zealand, with a primary thesis being that savings banks in New Zealand were intended to operate in a similar way to those in the UK. That is, to provide banking services to the working classes and supply revenue to a cash-strapped government. Savings banks were reasonably successful in meeting the needs of their depositors but provided little revenue to the government. This gives rise to a secondary thesis that, when the Government was presented with the opportunity to establish the Post Office Savings Bank (POSB), they did so with revenue in mind. Design/methodology/approach: Contemporaneous scholarly discussion along with newspaper, primary sourced bank and government archives builds an interpretation of why savings banks were established in New Zealand. This interpretation is presented in the form of a narrative, which tells the story of the rise of private savings banks in New Zealand and their eventual stagnation when the POSB was introduced. Findings: Savings banks in New Zealand were initiated by Governor Grey primarily to provide an alternative source of development funding. New Zealand savings banks, initially modelled on UK and New South Wales variants, also appear to have been designed to meet the needs of the working classes, with deposits limited to £50 a year and a maximum balance set of £100 in total. However, as the requirement to invest in Government debt was removed from their founding legislation, they mainly provided mortgages to their local communities. To some extent, this situation was remedied in 1867 when the POSB was established, as it was required to invest as directed by the Government. Originality/value: The narrative highlights the importance of savings banks and the POSB to both the people and government of New Zealand. This research adds to the discussion surrounding the purpose of savings banks and details the contributions made by both savings banks and the POSB in colonial New Zealand. As previous publications were in the main commissioned by various savings banks, this work provides an independent academic analysis of the first savings banks in colonial New Zealand in the period from the signing of the Treaty of Waitangi in 1840 until New Zealand became a dominion in 1907.